2017
DOI: 10.11645/11.1.2184
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy and informed learning:

Abstract: Article Bruce et al. 2017. Information literacy and informed learning: conceptual innovations for IL research and practice futures. Journal of Information Literacy, 11(1), pp.4-22. http://dx. AbstractOur paper draws together conceptual innovations emerging from the work of a group of researchers focussed on the relational approach to information literacy (IL), more recently labelled 'informed learning'. Team members have been working together in various configurations for periods ranging from seven to seventee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 31 publications
2
22
0
2
Order By: Relevance
“…Elham will discuss the two‐phase qualitative and participatory “information experience design” research approach which bridges theory to practice in the information use domain (Bruce et al , Sayyad Abdi, , Sayyad Abdi et al, ). Elham will describe a qualitative investigation into immigrants' experience of “information use to learn” and how the analysis was used to inform the design of enabling interventions (e.g.…”
Section: Panelistsmentioning
confidence: 99%
“…Elham will discuss the two‐phase qualitative and participatory “information experience design” research approach which bridges theory to practice in the information use domain (Bruce et al , Sayyad Abdi, , Sayyad Abdi et al, ). Elham will describe a qualitative investigation into immigrants' experience of “information use to learn” and how the analysis was used to inform the design of enabling interventions (e.g.…”
Section: Panelistsmentioning
confidence: 99%
“…Although building upon longitudinal North American studies that demonstrated the efficacy of information-centred (Bruce et al, 2017) and systems-focused (Checkland, 2011) design activities in the workplace (e.g. Mirijamdotter and Somerville, 2009;Somerville, 2009Somerville, , 2015cSomerville and Mirijamdotter, 2014), this UBT initiative commenced at a graduate level systems analysis, design and modelling course 2 that aimed to ultimately redesign university educational experience.…”
Section: Research Papermentioning
confidence: 99%
“…Az információs túlterhelés szempontjából nem lényegtelen, hogy ebben a keretben információ alatt bármilyen, egy adott kontextusban informáló élményt érthetünk, tehát lehet tény, elmélet, modell, hang, testbeszéd vagy éppen tudományos eredmény, amely keletkezhet a természetben vagy a virtuális világban (Bruce et al 2017).…”
Section: Egy "öRökzöld Téma": Az Információs Túlterhelésunclassified